A New Host Record for the Egg Parasitoid Anagrus nigriventris (Hymenoptera: Mymaridae) of the Corn Leafhopper, Dalbulus maidis (Hemiptera: Cicadellidae) - Luft Albarracin, Erica Beatriz (2006)
A survey of the eggs parasitoids of the corn leafhopper, Dalbulus maidis (DeLong & Wolcott) was carried out in Tucumán Province, Argentina. Samples were collected during the summer of 2004-2005 with sentinel eggs. Anagrus nigriventris Girault was responsible for 7.2% of the total egg parasitism. That is the first record of this parasitoid reared from the eggs of D. maidis; A. nigriventris is one of three species of Anagrus known to affect populations of this leafhopper pest in Argentina.